2018
DOI: 10.1177/1744806918814367
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxystilbene glucoside relieves the chronic inflammatory pain by inhibiting neuronal apoptosis, microglia activation, and GluN2B overexpression in anterior cingulate cortex

Abstract: Tetrahydroxystilbene glucoside (THSG) is one of the active ingredients of Polygonum multiflorum. It has been shown to exert a variety of pharmacological effects, including antioxidant, anti-aging, and anti-atherosclerosis. Because of its prominent anti-inflammatory effect, we explored whether THSG had analgesic effect. In this study, we used a model of chronic inflammatory pain caused by injecting complete Freund’s adjuvant into the hind paw of mice. We found THSG relieved swelling and pain in the hind paw of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Treatment with SP could relieve anxiety-like symptoms in CFA-injected mice and reduce the levels of pro-inflammatory cytokines, which is consistent with previous findings showing that SP exerts anti-inflammatory effects. Moreover, previous studies have demonstrated that CFA injection activates the microglia, the primary inflammatory mediators and main source of cytokines in the CNS [23]. The same was observed in the current study, and SP was found to reduce CFA-induced microglial activation in the BLA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Treatment with SP could relieve anxiety-like symptoms in CFA-injected mice and reduce the levels of pro-inflammatory cytokines, which is consistent with previous findings showing that SP exerts anti-inflammatory effects. Moreover, previous studies have demonstrated that CFA injection activates the microglia, the primary inflammatory mediators and main source of cytokines in the CNS [23]. The same was observed in the current study, and SP was found to reduce CFA-induced microglial activation in the BLA.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, scopoletin suppresses p-JNK and p-p38 MAPKs, which may act alone or relate to the activation of NF-κB [18]. Our previous studies have shown that the expression of NF-κB p65, p-p38, and p-JNK MAPKs is increased in mice with chronic inflammation induced by CFA [23,49]. These alterations were consistently confirmed in the present work, while SP treatment effectively reversed these alterations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several pharmacological tools targeting glutamatergic signaling induce antinociceptive and/or anxiolytic effects in inflammation, presumably by inhibiting the upregulation of GluR1, NR2A, and NR2B in the ACC, as well as by reducing microglia and astrocyte activation and the induction of proinflammatory cytokines [261][262][263]. However, since these potential drugs are so far not directly applied to the ACC, accounting for other effects is challenging and more specific approaches are necessary to target specific neuron populations and their locations within defined brain regions to provide more mechanistic understanding.…”
Section: Glutamatementioning
confidence: 99%
“…Management of chronic pain remains a major medical challenge (Duan et al., 2018). Chronic pain has a negative impact on patient's life by altering general functions and activity, often affecting the prognosis of patients (Fan et al., 2018; Li et al., 2019; Xu et al., 2019). Inflammatory pain is a result of peripheral tissue damage and persistent inflammation and characterized by allodynia and hyperalgesia both at the site of damage and in adjacent tissue.…”
Section: Introductionmentioning
confidence: 99%